Strategi Pemberdayaan Alumni Pondok Pesantren AL-HASAN Tengginah Proppo Pamekasan - Imam Basofi; Fatimatus Zahro (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Islamic boarding schools play an active role in empowering alumni as a form of social responsibility to the community. In addition to functioning as Islamic educational institutions, Islamic boarding schools also actively develop the economic and da'wah fields in order to expand their contribution to the social life of the community. This study aims to describe the strategic planning for the empowerment of Al-Hasan Islamic boarding school alumni and to describe the implementation of the empowerment of Al-Hasan alumni. This research uses a qualitative descriptive approach, with data collection techniques through interviews, observation, and documentation. The results of this study show that 1) the planning strategy is through the formulation of objectives and the identification of the readiness of resources for each da'wah and economic programme. 2) The implementation of alumni empowerment is through empowerment in the fields of da'wah and economics.